2015
DOI: 10.1021/acs.jpcc.5b05510
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adsorption and Intercalation of Orange-Type Dyes into Mg–Al Layered Double Hydroxide

Abstract: In the context of depollution and textile wastewater treatment, the sorption-based processes are good candidates to achieve the efficient removal of such toxics substances as dyes. In the present study, the exchange−adsorption from aqueous solutions of three azoic dyes, Methyl Orange (MO), Orange II (OII), and Orange G (OG), onto Mg−Al−LDH−NO 3 layered double hydroxides (LDH, molar Mg:Al ratio of 2) was investigated through monitoring all retained and removed species in combination with direct calorimetry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 42 publications
(97 reference statements)
6
82
1
1
Order By: Relevance
“…32 An adsorption maximum of 1800 mg g À1 was reported for methyl orange using inorganic Mg-Al layered double hydroxide. 33 Due to the high variety of studied dyes and adsorption experimental setups found in the literature, a direct comparison between the different adsorbents might not be meaningful (e.g., no correlation was found between the amount of charged groups in dyes and the adsorption maximum of glutaraldehyde crosslinked chitosan). 29 However, it can be concluded that the anionic dye adsorption capacity of ICC1 is among the highest reported for organic and inorganic materials.…”
Section: Resultsmentioning
confidence: 99%
“…32 An adsorption maximum of 1800 mg g À1 was reported for methyl orange using inorganic Mg-Al layered double hydroxide. 33 Due to the high variety of studied dyes and adsorption experimental setups found in the literature, a direct comparison between the different adsorbents might not be meaningful (e.g., no correlation was found between the amount of charged groups in dyes and the adsorption maximum of glutaraldehyde crosslinked chitosan). 29 However, it can be concluded that the anionic dye adsorption capacity of ICC1 is among the highest reported for organic and inorganic materials.…”
Section: Resultsmentioning
confidence: 99%
“…Ln qe = ln kF + 1 ln Ce (4) Where, qmax and kL are Langmuir constants, kF and n are Freundlich constants with n giving an indication of favorable the adsorption process and verify the type of adsorption process. The isotherm adsorption parameters were shown in Table 3.…”
Section: Effect Of Temperature and Isotherm Modelingmentioning
confidence: 99%
“…Textile wastewater is a complex mixture and contains a highly polluting substance, i.e., heavy metal cations, and dye 3 . Most of dyes substance contained aromatic structure, which makes them toxic 4 , non-biodegradable, and also carcinogenic for humans and the environment 5,6 . In the environment, these colored effluent's was covering the surface of waters and reduced the oxygen 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is proposed to extract Evans Blue using Zn-Al LDH [20], Orange-type dyes -using Zn-Al LDH [21], Perylenediimide -using Zn-Al, Co-Al, Ni-Al LDH [22]. Various azo-dyes [23], including Remazol Brilliant Violet [24], had been extracted using Ni-Al LDH, blue dyes (including Maya Blue) [ [20,26] and intercalation [24]. However, the pigment preparation was not the aim of the study.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…1) synthesis of LDH with inorganic anions, using coprecipitation at high supersaturation [11,16,17], coprecipitation at constant рН [9,24], homogeneous coprecipitation [37], etc. ;…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%